Avaliação de programa para capacitar pais como agentes de promoção de comportamentos de estudo - Coser, Danila Secolim (Universidade Federal de São Carlos, 2009)
Parental involvement can be crucial for children s academic success; however, parents often don t have appropriate repertoire to deal with scholar difficulties or to promote autonomous and effective study behaviors in their children. The purpose of this study is to develop and evaluate an intervention program with children s guardians, particularly of those children with a history of low school performance. Participated in the research three guardians of children (two mothers and one grandfather), indicated by teachers as having learning difficulties, which were submitted to the Teaching Program, and also the teachers and the children, who studied at a municipal elementary school in a small town of the state of São Paulo. Initially, information was collected in order to determine the starting repertoire of the apprentices in the teaching program, through interviews with the children, their parents and teachers. The Teaching Program consisted of eight meetings in which was presented information and examples of aspects that promote the behavior of studying at home, in addition to several exercises for evaluation of performance and homework proposals regarding the themes discussed in the program. The parents received an instructional material to help with the explanation of teaching units and suggested activities. Due to holidays in the end of the school year, the intervention meetings were interrupted after the fourth session, but resumed in 60 days. On resumption, the parents were re-interviewed and responded to questions of true or false, concerning the units discussed up to that moment. Teachers, who had finished the school year, were also submitted to an interview. After the completion of the Teaching Program, information was collected as measures of post-test through interviews with parents, children and teachers of the new school year. In addition to the interview, the parents answered a questionnaire of satisfaction about the Teaching Program and a general simulation exercise. A follow-up interview was conducted six months after the post-test, again with the parents, teachers and children, and the parents also went through a new simulation for performance verification. The results show that the program enables the identification of changes in the repertoire of the parents in dealing with the children s study and/or the daily routine of interaction in the family environment, especially for one of the three participants in the period between the pre and post-test. Little evidence of maintenance of these changes was observed in the follow-up interviews. Some indication of improvement in the behavior of study and school performance of children, even minor, could also be identified in the teachers report. The discussion highlights the variables that may be important to understand these results and to advance in the creation of strategies for development, implementation and evaluation of Teaching Programs that are effective for teaching parents to promote appropriate study behaviors in children in order to promote appropriate study repertoires, as well as overcome and prevent school failure.
Keywords: Educação especial; Treinamento de pais; Técnicas de estudo - pais; Rendimento escolar; Comportamento de estudo; Parents training; Study behavior; Low school performance; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL